2014
DOI: 10.1007/s10554-014-0536-3
|View full text |Cite
|
Sign up to set email alerts
|

Left and right atrial phasic function and deformation in untreated patients with prediabetes and type 2 diabetes mellitus

Abstract: To evaluate phasic function and deformation of the left atrium (LA) and right atrium (RA) in subjects with prediabetes and type 2 diabetes mellitus. This cross-sectional study included 50 untreated normotensive subjects with prediabetes, 60 recently diagnosed normotensive diabetic patients and 60 healthy controls of similar sex and age. All the subjects underwent laboratory analyses and complete echocardiographic examination including strain analysis. LA and RA reservoir and conduit function gradually decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
3
47
2
1
Order By: Relevance
“…LA conduit function is correlated with LV early diastolic function [29], LA reservoir function is correlated with LV systolic function [30, 31], and LA pump function is associated with LV late diastolic function [32, 33]. The result of our study had agreed to these above.…”
Section: Discussionsupporting
confidence: 77%
“…LA conduit function is correlated with LV early diastolic function [29], LA reservoir function is correlated with LV systolic function [30, 31], and LA pump function is associated with LV late diastolic function [32, 33]. The result of our study had agreed to these above.…”
Section: Discussionsupporting
confidence: 77%
“…Acar et al did not report any difference in the 3DE LA total emptying volume; however, they detected increased active and decreased passive emptying fractions (7). Similar findings were reported from our research group (8). …”
supporting
confidence: 93%
“…In a prior study, Acar et al (7) did not show any difference in 3DE LA volume indices between type 1 DM patients and controls. Our study group reported that 3DE LA volumes were higher in subjects with type 2 DM; however, after adjustment for body size, these differences disappeared (8). …”
mentioning
confidence: 74%
“…Findings from our group show that left and right atrial reservoir and conduit function, assessed by emptying fractions and strain, are decreased among subjects with prediabetes and patients with diabetes compared with controls [14]. On the other hand, left and right atrial pump function increased in the same direction.…”
Section: Atrial Electromechanical Remodellingmentioning
confidence: 57%